Graphene coated hard carbon negative electrode material and preparation method thereof

Through the preparation method of graphene-coated hard carbon negative electrode material, the problems of capacity attenuation and poor conductivity caused by poor surface coating are solved, and higher cycle stability and conductivity are achieved.

CN119660717AActive Publication Date: 2025-03-21LUOYANG NEW ENERGY TECHNOLOGY DEVELOPMENT GROUP CO LTD

Patent Information

Application Number
CN202510187222.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-20
Publication Date
2025-03-21
Estimated Expiration
2045-02-20

AI Technical Summary

Technical Problem

The existing hard carbon anode materials have fast capacity decay and poor conductivity during the cycle process, mainly due to poor treatment of hard carbon materials and uneven surface coating.

Method used

The preparation method of graphene-coated hard carbon negative electrode material includes the preparation of microbial adsorption hard carbon material and the chemical vapor deposition, impregnation and annealing of graphene to form a uniform and dense graphene cladding layer.

Benefits of technology

Through the formation of the graphene cladding layer, the cyclic stability and conductivity of the hard carbon negative electrode material are significantly improved, capacity attenuation is delayed, and the structural stability of the material is enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a graphene-coated hard carbon negative electrode material and a preparation method thereof, and belongs to the technical field of hard carbon negative electrode materials. The preparation method of the graphene-coated hard carbon negative electrode material comprises the following steps: carrying out pretreatment and three-step soaking on coconut shells, carrying out biomass carbonization, mixing with a microbial suspension, and adsorbing to obtain a microbial adsorption type hard carbon material; and then carrying out surface treatment, chemical vapor deposition, impregnation, secondary chemical vapor deposition and annealing treatment on the microbial adsorption type hard carbon material to obtain the graphene coated hard carbon negative electrode material. The negative electrode material prepared by the method is high in first discharge capacity, high in first coulombic efficiency and good in cycle performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of hard carbon negative electrode materials, and in particular relates to a graphene-coated hard carbon negative electrode material and a preparation method thereof. Background Art

[0002] With the continuous development of modern science and technology, the over-exploitation and utilization of traditional fossil energy such as coal, oil and natural gas will inevitably cause energy crisis and environmental pollution problems. In recent years, green, cheap new renewable sustainable energy, including solar energy, biomass energy, geothermal energy, wind energy, tidal energy, etc., has received widespread attention from scientists. However, these new energy sources, which are heavily dependent on weather, seasons and locations, have the characteristics of intermittent and instability. In order to achieve continuous and stable power output, they need to be converted into electrical energy and then stored in large-scale power storage systems. Therefore, the development of efficient and convenient large-scale energy storage technology plays a vital role in the development and utilization of new energy.

[0003] As the key carrier of large-scale energy storage technology, the performance of batteries directly affects the energy storage effect. As an important component of batteries, negative electrode materials play a decisive role in the overall performance of batteries. Finding high-performance negative electrode materials has become a key link in improving battery energy storage capacity and promoting the development of large-scale energy storage technology. Among the many negative electrode materials, hard carbon has gradually attracted the attention of the industry due to its unique and superior performance and application potential.

[0004] Hard carbon negative electrode materials have played a significant role in improving battery energy storage performance, improving safety, reducing costs, etc., and are widely used in lithium-ion batteries and sodium-ion batteries, and then widely used in the field of new energy vehicles. Therefore, the present invention develops a graphene-coated hard carbon negative electrode material and a preparation method thereof, which are used to solve the technical problems in the prior art that the capacity of hard carbon negative electrode materials decays rapidly and the conductivity is poor during the cycle due to poor treatment of hard carbon materials and uneven coating on the surface of hard carbon materials. Summary of the invention

[0005] The purpose of the present invention is to provide a graphene-coated hard carbon negative electrode material and a preparation method thereof, so as to solve the technical problems in the prior art that the hard carbon negative electrode material has a fast capacity decay and poor conductivity during the cycle due to poor treatment of the hard carbon material and uneven surface coating of the hard carbon material.

[0006] In order to achieve the above object, the present invention adopts the following technical solutions: A method for preparing a graphene-coated hard carbon negative electrode material comprises the following steps: (1) Preparation of microbial adsorption hard carbon material: After pretreatment and three-step soaking, coconut shell is carbonized and then mixed with microbial suspension for adsorption to obtain microbial adsorption hard carbon material; (2) Graphene coating: The microbial adsorption hard carbon material is subjected to surface treatment, chemical vapor deposition, impregnation, chemical vapor deposition again and annealing to obtain a graphene-coated hard carbon negative electrode material.

[0007] Furthermore, the method for preparing the graphene-coated hard carbon negative electrode material, step (1) comprises the following process: S1. Coconut shell pretreatment: The coconut shell is washed with deionized water, then immersed in a surfactant solution, ultrasonically cleaned, and then dried to obtain a clean coconut shell; S2, three-step soaking: soak the clean coconut shell in HCl solution, rinse with deionized water until neutral, soak in NaOH solution, rinse with deionized water until neutral, soak in catalyst solution, rinse with deionized water, dry, and obtain chemically treated coconut shell; S3, carbonization: heating the chemically treated coconut shell in nitrogen or argon, keeping the temperature, to obtain a hard carbon material; S4. Microbial adsorption: The hard carbon material is dispersed in a microbial suspension, stirred for adsorption, and after completion, dried and carbonized under an inert atmosphere to obtain a microbial adsorption type hard carbon material.

[0008] Furthermore, S1 is washed with deionized water for 2-3 times, the surfactant solution is an equal volume mixture of sodium dodecylbenzene sulfonate solution and polyoxyethylene octylphenol ether solution, the mass concentration of sodium dodecylbenzene sulfonate solution is 0.2-0.8wt%, the mass concentration of polyoxyethylene octylphenol ether solution is 0.3-1wt%, the ultrasonic cleaning time is 1-2 hours, the drying temperature is 60-80°C, and the drying time is 12-24 hours; the concentration of HCl solution in S2 is 0.1-1mol / L, the concentration of NaOH solution is 0.1-1mol / L, the soaking time is 2-4 hours, and the catalyst solution is composed of ferric nitrate and nickel nitrate in a mass ratio of 1-2: 1-2 is mixed and prepared, the mass concentration of the catalyst solution is 0.8-3wt%, the catalyst solution is immersed for 12-24 hours, the drying temperature is 60-80°C, and the drying time is 12-24 hours; S3 is heated to 800-1200°C, the heating rate is 2-4°C / min, and the insulation time is 1-3 hours; S4 is a microbial suspension of equal amounts of Rhizopus and Penicillium, the dry weight concentration of the mycelium is 0.5-2g / L, the adsorption time is 12-24 hours, the inert atmosphere is nitrogen or argon, the carbonization temperature is 800-1200°C, the heating rate is 2-4°C / min, and the insulation time is 1-3 hours.

[0009] Furthermore, the method for preparing the graphene-coated hard carbon negative electrode material, step (2) comprises the following process: M1. Surface treatment of hard carbon: soaking the microbial adsorption hard carbon material in a mixed acid solution, then washing it with deionized water until it is neutral, and drying it to obtain an acid-leached hard carbon material, and then placing the acid-leached hard carbon material in a plasma treatment device, introducing oxygen and argon to obtain an activated hard carbon material; M2. Primary chemical vapor deposition: placing the activated hard carbon material into a quartz boat of a chemical vapor deposition reactor, placing the quartz boat into the heating area of ​​the reactor, closing the reactor, introducing argon gas first, purging the reactor, raising the temperature, and when the temperature reaches the set value, keeping the temperature, and then introducing carbon source gas and hydrogen gas. When the reaction is finished, closing the carbon source gas, continuing to introduce hydrogen and argon gas, and cooling down. When the reactor is cooled to room temperature, a primary graphene-coated hard carbon material is obtained; M3. Impregnation: completely immersing the primary graphene-coated hard carbon material into a polyvinylidene fluoride solution, taking it out, drying it, and repeating the immersion to obtain an impregnated and coated hard carbon material; M4, secondary chemical vapor deposition: repeating process M2 to obtain secondary graphene-coated hard carbon material; M5. Annealing treatment: placing the graphene-coated hard carbon material into a high-temperature furnace, and performing annealing treatment under an argon or nitrogen protective atmosphere to obtain a graphene-coated hard carbon negative electrode material.

[0010] Further, the mixed acid solution in M1 is prepared by mixing concentrated sulfuric acid and concentrated nitric acid in a volume ratio of 3:1, the drying temperature is 60-80°C, the drying time is 12-24 hours, the plasma treatment time is 5-10 minutes, the gas flow rate is 20-50sccm, and the plasma power is 50-150W; the flow rate of argon in M2 is controlled at 200-500sccm, the time for purging the reactor is 15-30 minutes, the heating rate is 5-10°C / min, the temperature is raised to 900-1000°C, and when the temperature reaches the set value, it is kept warm for 10-15 minutes, and the carbon source gas is methane or ethylene, the volume ratio of carbon source gas to hydrogen is 1:10-20, the total gas flow rate is 100-300sccm, the reaction time is 30-60 minutes, and the cooling rate is 5-10°C / min; the polyvinylidene fluoride solution in M3 is prepared by dissolving polyvinylidene fluoride in N-methylpyrrolidone, the mass concentration of the polyvinylidene fluoride solution is 5-15wt%, the immersion time is 10-30 minutes, the drying temperature is 80-100°C, the drying time is 10-16 hours, and the immersion is repeated 2-3 times; the annealing temperature in M5 is 300-500°C, and the annealing time is 1-3 hours.

[0011] In summary, due to the adoption of the above technical solution, the beneficial effects of the present invention are: 1. The present invention performs biomass carbonization on coconut shells after pretreatment and three-step soaking, and then mixes and adsorbs with a microbial suspension to obtain a microbial adsorption hard carbon material, wherein the HCl solution can dissolve some alkaline impurities such as metal oxides and carbonates in the coconut shells, and can also etch the surface of the coconut shells to increase its specific surface area and surface roughness, which is beneficial to the adsorption and reaction of subsequent substances; the NaOH solution can react with lignin, hemicellulose, etc. in the coconut shells to make the structure of the coconut shells looser, further increase the specific surface area, and also provide more active sites for the subsequent catalyst loading; iron and nickel can catalyze the rearrangement of carbon atoms and graphite during the carbonization process The carbonization process helps to form a hard carbon material with good crystal structure and conductivity. In addition, microorganisms have the ability to adsorb and metabolize organic matter. Rhizopus and Penicillium can grow and adsorb on the surface and pores of hard carbon materials. Mycelium can be wrapped around hard carbon particles to form a network structure, which increases the specific surface area and porosity of the material. At the same time, microorganisms will secrete some organic matter during their growth, which can be further carbonized into carbonaceous materials during the carbonization process, thereby improving the performance of hard carbon materials. Finally, the carbonaceous materials formed after microbial carbonization are intertwined with the original hard carbon materials, which increases the structural stability and conductivity of the material, and also provides more active sites and channels for the storage of sodium ions.

[0012] 2. The present invention uses surface treatment of microbial adsorption type hard carbon materials. First, immersing them in mixed acid can remove impurities, oil stains and some amorphous carbon on the hard carbon surface. At the same time, introducing oxygen-containing functional groups such as carboxyl and hydroxyl groups on the hard carbon surface not only increases the active sites on the hard carbon surface, but also helps to uniformly coat the subsequent graphene. Secondly, oxygen plasma in plasma treatment can etch the hard carbon surface, increase the surface roughness, and improve the surface energy. Argon plasma can clean and bombard the hard carbon surface, further remove surface pollutants, and at the same time create more defects and active centers on the surface, which is beneficial to the adsorption and decomposition of the carbon source gas in the subsequent chemical vapor deposition process.

[0013] 3. The present invention uses chemical vapor deposition to nucleate the carbon atoms produced by the pyrolysis of the carbon source gas on the surface of the hard carbon material and grow them into a graphene layer. The graphene layer is tightly coated on the surface of the hard carbon particles to form a continuous conductive network. In addition, through the impregnation of polyvinylidene fluoride solution, polyvinylidene fluoride can be filled between the graphene layer and the hard carbon material and in the pores of the graphene layer, playing a bonding and protective role, enhancing the overall structural stability of the material, and also helping to inhibit the side reactions between the electrode material and the electrolyte. Secondary vapor deposition can further improve the graphene coating layer, making the coating more uniform and dense, enhancing the conductivity and structural integrity of the electrode material, thereby improving the rate performance and cycle stability of the negative electrode material. DETAILED DESCRIPTION

[0014] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0015] Example 1: This example discloses a method for preparing a graphene-coated hard carbon negative electrode material, comprising the following steps: (1) Preparation of microbial adsorption hard carbon material: After pretreatment and three-step soaking, coconut shell is carbonized and then mixed with microbial suspension for adsorption to obtain microbial adsorption hard carbon material; (2) Graphene coating: The microbial adsorption hard carbon material is subjected to surface treatment, chemical vapor deposition, impregnation, chemical vapor deposition again and annealing to obtain a graphene-coated hard carbon negative electrode material.

[0016] Wherein, the preparation method of the graphene-coated hard carbon negative electrode material, step (1) comprises the following process: S1, coconut shell pre-treatment: the coconut shell is washed with deionized water twice, and then immersed in a surfactant solution, the surfactant solution is an equal volume mixture of a sodium dodecylbenzene sulfonate solution and a polyoxyethylene octylphenol ether solution, the mass concentration of the sodium dodecylbenzene sulfonate solution is 0.2wt%, and the mass concentration of the polyoxyethylene octylphenol ether solution is 0.3wt%, ultrasonic cleaning for 1 hour, after the end, drying, the drying temperature is 60 ° C, and the drying time is 12 hours to obtain a clean coconut shell; S2, three-step soaking: clean coconut shells are soaked in 0.1mol / L HCl solution for 2 hours, rinsed with deionized water to neutrality, put into 0.1mol / L NaOH solution and soaked for 2 hours, then rinsed with deionized water to neutrality, and then soaked in a catalyst solution, wherein the catalyst solution is prepared by mixing ferric nitrate and nickel nitrate in a mass ratio of 1:2, the mass concentration of the catalyst solution is 0.8wt%, and the catalyst solution is soaked for 12 hours, rinsed with deionized water, dried, the drying temperature is 60°C, and the drying time is 12 hours to obtain chemically treated coconut shells; S3, carbonization: heating the chemically treated coconut shell to 800°C in nitrogen or argon at a rate of 2°C / min, and keeping the temperature for 1 hour to obtain a hard carbon material; S4. Microbial adsorption: disperse the hard carbon material in a microbial suspension, which is an equal mixture of Rhizopus and Penicillium, and the dry weight concentration of mycelium is 0.5g / L. Stir and adsorb for 12 hours. After the adsorption, dry and carbonize under nitrogen or argon at a carbonization temperature of 800°C and a heating rate of 2°C / min. Keep warm for 1 hour to obtain a microbial adsorption type hard carbon material.

[0017] Wherein, the preparation method of the graphene-coated hard carbon negative electrode material, step (2) comprises the following process: M1. Surface treatment of hard carbon: soak the microbial adsorption type hard carbon material in a mixed acid solution, wherein the mixed acid solution is prepared by mixing concentrated sulfuric acid and concentrated nitric acid in a volume ratio of 3:1, then wash with deionized water until neutral, dry at a drying temperature of 60°C and a drying time of 12 hours to obtain an acid-leached hard carbon material, and then place the acid-leached hard carbon material in a plasma treatment device, introduce oxygen and argon, and the plasma treatment time is 5 minutes, the gas flow rate is 20 sccm, and the plasma power is 50 W to obtain an activated hard carbon material; M2. One-time chemical vapor deposition: put the activated hard carbon material into a quartz boat of a chemical vapor deposition reactor, put the quartz boat into the heating area of ​​the reactor, turn off the reactor, first introduce argon, the flow rate of argon is controlled at 200 sccm, purge the reactor, the purge time is 15 minutes, heat up, the heating rate is 5°C / min, heat up to 900°C, when the temperature reaches the set value, keep warm for 10 minutes, then introduce methane and hydrogen, the volume ratio of carbon source gas to hydrogen is 1:10, the total gas flow rate is 100 sccm, the reaction time is 30 minutes, turn off the carbon source gas, continue to introduce hydrogen and argon, cool down, the cooling rate is 5°C / min, wait for the reactor to cool to room temperature, and obtain a graphene-coated hard carbon material; M3. Impregnation: completely immerse the primary graphene-coated hard carbon material in a polyvinylidene fluoride solution, wherein the polyvinylidene fluoride solution is prepared by dissolving polyvinylidene fluoride in N-methylpyrrolidone, the mass concentration of the polyvinylidene fluoride solution is 5wt%, the immersion time is 10 minutes, take out, dry, the drying temperature is 80°C, the drying time is 10 hours, repeat the immersion twice, and obtain an impregnated coated hard carbon material; M4, secondary chemical vapor deposition: repeating process M2 to obtain secondary graphene-coated hard carbon material; M5. Annealing treatment: Put the graphene-coated hard carbon material into a high-temperature furnace and perform annealing treatment under an argon or nitrogen protective atmosphere. The annealing temperature is 300° C. and the annealing time is 1 hour to obtain a graphene-coated hard carbon negative electrode material.

[0018] Example 2: This example discloses a method for preparing a graphene-coated hard carbon negative electrode material, comprising the following steps: (1) Preparation of microbial adsorption hard carbon material: After pretreatment and three-step soaking, coconut shell is carbonized and then mixed with microbial suspension for adsorption to obtain microbial adsorption hard carbon material; (2) Graphene coating: The microbial adsorption hard carbon material is subjected to surface treatment, chemical vapor deposition, impregnation, chemical vapor deposition again and annealing to obtain a graphene-coated hard carbon negative electrode material.

[0019] Wherein, the preparation method of the graphene-coated hard carbon negative electrode material, step (1) comprises the following process: S1, coconut shell pre-treatment: the coconut shell was washed 3 times with deionized water, and then immersed in a surfactant solution, the surfactant solution was an equal volume mixture of a sodium dodecylbenzene sulfonate solution and a polyoxyethylene octylphenol ether solution, the mass concentration of the sodium dodecylbenzene sulfonate solution was 0.5wt%, and the mass concentration of the polyoxyethylene octylphenol ether solution was 0.7wt%, and ultrasonic cleaning was performed for 1.5 hours. After the end, the coconut shell was dried at 70 ° C and dried for 19 hours to obtain a clean coconut shell; S2, three-step soaking: clean coconut shells are soaked in 0.6mol / L HCl solution for 3 hours, rinsed with deionized water to neutrality, put into 0.5mol / L NaOH solution and soaked for 3 hours, then rinsed with deionized water to neutrality, and then soaked in a catalyst solution, wherein the catalyst solution is prepared by mixing ferric nitrate and nickel nitrate in a mass ratio of 1:1.5, the mass concentration of the catalyst solution is 2wt%, and the catalyst solution is soaked for 20 hours, rinsed with deionized water, dried, the drying temperature is 70°C, and the drying time is 18 hours to obtain chemically treated coconut shells; S3, carbonization: heating the chemically treated coconut shell to 1000°C in nitrogen or argon at a heating rate of 3°C / min for 2 hours to obtain a hard carbon material; S4. Microbial adsorption: disperse the hard carbon material in a microbial suspension, which is an equal mixture of Rhizopus and Penicillium, and the dry weight concentration of mycelium is 1.5g / L. Stir and adsorb for 20 hours. After the adsorption, dry and carbonize under nitrogen or argon at a carbonization temperature of 1000°C and a heating rate of 3°C / min. Keep warm for 2 hours to obtain a microbial adsorption type hard carbon material.

[0020] Wherein, the preparation method of the graphene-coated hard carbon negative electrode material, step (2) comprises the following process: M1. Surface treatment of hard carbon: soak the microbial adsorption type hard carbon material in a mixed acid solution, wherein the mixed acid solution is prepared by mixing concentrated sulfuric acid and concentrated nitric acid in a volume ratio of 3:1, then wash with deionized water until neutral, dry at a drying temperature of 70°C and a drying time of 18 hours to obtain an acid-leached hard carbon material, and then place the acid-leached hard carbon material in a plasma treatment device, introduce oxygen and argon, the plasma treatment time is 8 minutes, the gas flow rate is 40 sccm, and the plasma power is 100 W to obtain an activated hard carbon material; M2. One-time chemical vapor deposition: put the activated hard carbon material into a quartz boat of a chemical vapor deposition reactor, put the quartz boat into the heating area of ​​the reactor, turn off the reactor, first introduce argon, the flow rate of argon is controlled at 400 sccm, purge the reactor, the purge time is 25 minutes, heat up, the heating rate is 7°C / min, heat up to 950°C, when the temperature reaches the set value, keep warm for 13 minutes, then introduce methane and hydrogen, the volume ratio of carbon source gas to hydrogen is 1:15, the total gas flow rate is 200 sccm, the reaction time is 50 minutes, turn off the carbon source gas, continue to introduce hydrogen and argon, cool down, the cooling rate is 8°C / min, wait for the reactor to cool to room temperature, and obtain a graphene-coated hard carbon material; M3. Impregnation: completely immerse the primary graphene-coated hard carbon material in a polyvinylidene fluoride solution, wherein the polyvinylidene fluoride solution is prepared by dissolving polyvinylidene fluoride in N-methylpyrrolidone, the mass concentration of the polyvinylidene fluoride solution is 10wt%, the immersion time is 20 minutes, take out, dry, the drying temperature is 90°C, the drying time is 14 hours, and the immersion is repeated 3 times to obtain an impregnated coated hard carbon material; M4, secondary chemical vapor deposition: repeating process M2 to obtain secondary graphene-coated hard carbon material; M5. Annealing treatment: Put the graphene-coated hard carbon material into a high-temperature furnace and perform annealing treatment under an argon or nitrogen protective atmosphere. The annealing temperature is 400° C. and the annealing time is 2 hours to obtain a graphene-coated hard carbon negative electrode material.

[0021] Example 3: This example discloses a method for preparing a graphene-coated hard carbon negative electrode material, comprising the following steps: (1) Preparation of microbial adsorption hard carbon material: After pretreatment and three-step soaking, coconut shell is carbonized and then mixed with microbial suspension for adsorption to obtain microbial adsorption hard carbon material; (2) Graphene coating: The microbial adsorption hard carbon material is subjected to surface treatment, chemical vapor deposition, impregnation, chemical vapor deposition again and annealing to obtain a graphene-coated hard carbon negative electrode material.

[0022] Wherein, the preparation method of the graphene-coated hard carbon negative electrode material, step (1) comprises the following process: S1, coconut shell pre-treatment: the coconut shell was washed 3 times with deionized water, and then immersed in a surfactant solution, the surfactant solution was an equal volume mixture of a sodium dodecylbenzene sulfonate solution and a polyoxyethylene octylphenol ether solution, the mass concentration of the sodium dodecylbenzene sulfonate solution was 0.8wt%, and the mass concentration of the polyoxyethylene octylphenol ether solution was 1wt%, and ultrasonic cleaning was performed for 2 hours. After the end, the coconut shell was dried at 80 ° C and dried for 24 hours to obtain a clean coconut shell; S2, three-step soaking: clean coconut shells are soaked in 1mol / L HCl solution for 4 hours, rinsed with deionized water to neutrality, put into 1mol / L NaOH solution and soaked for 4 hours, then rinsed with deionized water to neutrality, and then soaked in a catalyst solution, wherein the catalyst solution is prepared by mixing ferric nitrate and nickel nitrate in a mass ratio of 1:1, the mass concentration of the catalyst solution is 3wt%, the catalyst solution is soaked for 24 hours, rinsed with deionized water, dried, the drying temperature is 80°C, and the drying time is 24 hours to obtain chemically treated coconut shells; S3, carbonization: heating the chemically treated coconut shell to 1200°C in nitrogen or argon at a heating rate of 4°C / min for 3 hours to obtain a hard carbon material; S4. Microbial adsorption: disperse the hard carbon material in a microbial suspension, which is an equal mixture of Rhizopus and Penicillium, and the dry weight concentration of mycelium is 2g / L. Stir and adsorb for 24 hours. After the adsorption, dry and carbonize under nitrogen or argon at a carbonization temperature of 1200°C and a heating rate of 4°C / min. Keep warm for 3 hours to obtain a microbial adsorption type hard carbon material.

[0023] Wherein, the preparation method of the graphene-coated hard carbon negative electrode material, step (2) comprises the following process: M1. Surface treatment of hard carbon: soak the microbial adsorption type hard carbon material in a mixed acid solution, wherein the mixed acid solution is prepared by mixing concentrated sulfuric acid and concentrated nitric acid in a volume ratio of 3:1, then wash with deionized water until neutral, dry at a drying temperature of 80°C and a drying time of 24 hours to obtain an acid-leached hard carbon material, and then place the acid-leached hard carbon material in a plasma treatment device, introduce oxygen and argon, and the plasma treatment time is 10 minutes, the gas flow rate is 50 sccm, and the plasma power is 150 W to obtain an activated hard carbon material; M2. One-time chemical vapor deposition: put the activated hard carbon material into a quartz boat of a chemical vapor deposition reactor, put the quartz boat into the heating area of ​​the reactor, turn off the reactor, first introduce argon, the flow rate of argon is controlled at 500sccm, purge the reactor, the purge time of the reactor is 30 minutes, heat up, the heating rate is 10°C / min, heat up to 1000°C, when the temperature reaches the set value, keep warm for 15 minutes, then introduce ethylene and hydrogen, the volume ratio of carbon source gas to hydrogen is 1:20, the total gas flow rate is 300sccm, the reaction time is 60 minutes, turn off the carbon source gas, continue to introduce hydrogen and argon, cool down, the cooling rate is 10°C / min, wait for the reactor to cool to room temperature, and obtain a one-time graphene-coated hard carbon material; M3. Impregnation: completely immerse the primary graphene-coated hard carbon material in a polyvinylidene fluoride solution, wherein the polyvinylidene fluoride solution is prepared by dissolving polyvinylidene fluoride in N-methylpyrrolidone, wherein the mass concentration of the polyvinylidene fluoride solution is 15 wt %, the immersion time is 30 minutes, the material is taken out, and dried at a drying temperature of 100° C. for 16 hours, and the immersion is repeated 3 times to obtain an impregnated and coated hard carbon material; M4, secondary chemical vapor deposition: repeating process M2 to obtain secondary graphene-coated hard carbon material; M5. Annealing treatment: Put the graphene-coated hard carbon material into a high-temperature furnace and perform annealing treatment under an argon or nitrogen protective atmosphere. The annealing temperature is 500° C. and the annealing time is 3 hours to obtain a graphene-coated hard carbon negative electrode material.

[0024] Comparative Example 1: Compared with Example 2, in Comparative Example 1, during the preparation process of the graphene-coated hard carbon negative electrode material, the three-step immersion treatment is not performed, and other conditions remain unchanged.

[0025] Comparative Example 2: Comparative Example 2 Compared with Example 2, in the preparation process of the graphene-coated hard carbon negative electrode material in Comparative Example 2, no microbial adsorption treatment is performed, and other conditions remain unchanged.

[0026] Comparative Example 3: Comparative Example 3 Compared with Example 2, in the preparation process of the graphene-coated hard carbon negative electrode material in Comparative Example 3, no polyvinylidene fluoride solution impregnation treatment is performed, and other conditions remain unchanged.

[0027] Experimental example: The performance of the graphene-coated hard carbon negative electrode materials prepared in Examples 1-3 and Comparative Examples 1-3 was tested. The graphene-coated hard carbon negative electrode materials, acetylene black and polyvinylidene fluoride prepared in Examples 1-3 and Comparative Examples 1-3 were mixed in an N-methylpyrrolidone solvent at a mass ratio of 8:1:1, and stirred evenly to form a slurry. The slurry was evenly coated on the copper foil current collector, and then dried at 100°C in a vacuum drying oven for 24 hours, and then punched into a circular electrode sheet with a diameter of 12 mm using a sheet punching machine. In a glove box filled with argon, a sodium sheet was used as a counter electrode, a polypropylene microporous membrane was used as a diaphragm, and the electrolyte was a solution of 1M NaPF6 dissolved in diethylene glycol dimethyl ether, and assembled into a button half-cell. A simulated battery test was carried out in a 5V, 10mA Xinwei battery test cabinet, with a charge and discharge voltage of 0.01-3.0V and a charge and discharge rate of 0.1C. The test results are shown in Table 1: Table 1

[0028] According to the test results in Table 1, it can be seen that the graphene-coated hard carbon negative electrode materials prepared in Examples 1-3 of the present invention have high first discharge capacity, high first coulombic efficiency and good cycle performance. By comparing Comparative Examples 1-3 with Examples 1-3, it can be seen that the first discharge capacity, first coulombic efficiency and cycle performance of the graphene-coated hard carbon negative electrode materials can be effectively improved by three-step immersion treatment, microbial adsorption treatment and polyvinylidene fluoride solution immersion treatment.

[0029] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

[0030] The preferred embodiments of the present invention disclosed above are only used to help explain the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to only specific implementation methods. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.

Claims

1. A method for preparing a graphene-coated hard carbon negative electrode material, characterized in that: The steps include: (1) Preparation of microbial adsorption hard carbon material: After pretreatment and three-step soaking, coconut shell is carbonized and then mixed with microbial suspension for adsorption to obtain microbial adsorption hard carbon material; (2) Graphene coating: The microbial adsorption hard carbon material is subjected to surface treatment, chemical vapor deposition, impregnation, chemical vapor deposition again and annealing to obtain a graphene-coated hard carbon negative electrode material.

2. The method for preparing the graphene-coated hard carbon negative electrode material according to claim 1, characterized in that: Step (1) includes the following process: S1. Coconut shell pretreatment: The coconut shell is washed with deionized water, then immersed in a surfactant solution, ultrasonically cleaned, and then dried to obtain a clean coconut shell; S2, three-step soaking: soak the clean coconut shell in HCl solution, rinse with deionized water until neutral, soak in NaOH solution, rinse with deionized water until neutral, soak in catalyst solution, rinse with deionized water, dry, and obtain chemically treated coconut shell; S3, carbonization: heating the chemically treated coconut shell in nitrogen or argon, keeping the temperature, to obtain a hard carbon material; S4. Microbial adsorption: The hard carbon material is dispersed in a microbial suspension, stirred for adsorption, and after completion, dried and carbonized under an inert atmosphere to obtain a microbial adsorption type hard carbon material.

3. The method for preparing the graphene-coated hard carbon negative electrode material according to claim 2, characterized in that: S1 is washed with deionized water for 2-3 times. The surfactant solution is an equal volume mixture of sodium dodecylbenzene sulfonate solution and polyoxyethylene octylphenol ether solution. The mass concentration of the sodium dodecylbenzene sulfonate solution is 0.2-0.8wt%, and the mass concentration of the polyoxyethylene octylphenol ether solution is 0.3-1wt%.

4. The method for preparing the graphene-coated hard carbon negative electrode material according to claim 2, characterized in that: The concentration of the HCl solution in S2 is 0.1-1 mol / L, the concentration of the NaOH solution is 0.1-1 mol / L, the immersion time is 2-4 hours, the catalyst solution is prepared by mixing ferric nitrate and nickel nitrate in a mass ratio of 1-2:1-2, the mass concentration of the catalyst solution is 0.8-3wt%, and the immersion time of the catalyst solution is 12-24 hours; S3 is heated to 800-1200°C, the heating rate is 2-4°C / min, and the insulation time is 1-3 hours.

5. The method for preparing the graphene-coated hard carbon negative electrode material according to claim 2, characterized in that: The microbial suspension in S4 is an equal mixture of Rhizopus and Penicillium, the dry weight concentration of the mycelium is 0.5-2g / L, the adsorption time is 12-24 hours, the inert atmosphere is nitrogen or argon, the carbonization temperature is 800-1200°C, the heating rate is 2-4°C / min, and the insulation time is 1-3 hours.

6. The method for preparing the graphene-coated hard carbon negative electrode material according to claim 1, characterized in that: Step (2) includes the following process: M1. Surface treatment of hard carbon: soaking the microbial adsorption hard carbon material in a mixed acid solution, then washing it with deionized water until it is neutral, and drying it to obtain an acid-leached hard carbon material, and then placing the acid-leached hard carbon material in a plasma treatment device, introducing oxygen and argon to obtain an activated hard carbon material; M2. Primary chemical vapor deposition: placing the activated hard carbon material into a quartz boat of a chemical vapor deposition reactor, placing the quartz boat into the heating area of ​​the reactor, closing the reactor, introducing argon gas first, purging the reactor, raising the temperature, and when the temperature reaches the set value, keeping the temperature, and then introducing carbon source gas and hydrogen gas. When the reaction is finished, closing the carbon source gas, continuing to introduce hydrogen and argon gas, and cooling down. When the reactor is cooled to room temperature, a primary graphene-coated hard carbon material is obtained; M3. Impregnation: completely immersing the primary graphene-coated hard carbon material into a polyvinylidene fluoride solution, taking it out, drying it, and repeating the immersion to obtain an impregnated and coated hard carbon material; M4, secondary chemical vapor deposition: repeating process M2 to obtain secondary graphene-coated hard carbon material; M5. Annealing treatment: placing the graphene-coated hard carbon material into a high-temperature furnace, and performing annealing treatment under an argon or nitrogen protective atmosphere to obtain a graphene-coated hard carbon negative electrode material.

7. The method for preparing the graphene-coated hard carbon negative electrode material according to claim 6, characterized in that: The mixed acid solution in M1 is prepared by mixing concentrated sulfuric acid and concentrated nitric acid in a volume ratio of 3:1, the drying temperature is 60-80°C, the drying time is 12-24 hours, the plasma treatment time is 5-10 minutes, the gas flow rate is 20-50sccm, and the plasma power is 50-150W.

8. The method for preparing the graphene-coated hard carbon negative electrode material according to claim 6, characterized in that: The flow rate of argon in M2 is controlled at 200-500sccm, the time for purging the reactor is 15-30 minutes, the heating rate is 5-10°C / min, the temperature is raised to 900-1000°C, and when the temperature reaches the set value, it is kept warm for 10-15 minutes. The carbon source gas is methane or ethylene, the volume ratio of the carbon source gas to hydrogen is 1:10-20, the total gas flow rate is 100-300sccm, the reaction time is 30-60 minutes, and the cooling rate is 5-10°C / min.

9. The method for preparing the graphene-coated hard carbon negative electrode material according to claim 6, characterized in that: The polyvinylidene fluoride solution in M3 is prepared by dissolving polyvinylidene fluoride in N-methylpyrrolidone, the mass concentration of the polyvinylidene fluoride solution is 5-15wt%, the immersion time is 10-30 minutes, and the immersion is repeated 2-3 times; the annealing temperature in M5 is 300-500°C, and the annealing time is 1-3 hours.

10. A graphene-coated hard carbon negative electrode material, characterized in that: The negative electrode material is prepared by the method for preparing the graphite-coated hard carbon negative electrode material as described in any one of claims 1 to 9.

Citation Information

Patent Citations

  • Method for preparing thin-layer graphene negative electrode active material by utilizing antibiotic bacterium dregs

    CN112225203A

  • Preparation method and application of mycelium-based carbon film conductive skeleton and method for preparing battery

    CN114188540A

  • Hard carbon negative electrode material, preparation method thereof and battery containing hard carbon negative electrode material

    CN114804068A

  • Phosphorus-doped microorganism modified biomass carbon material, preparation method and application

    CN116002661A

  • Hard carbon negative electrode material for sodium ion battery and preparation method of hard carbon negative electrode material

    CN116169238A

Cited By

  • Method for preparing hard carbon negative electrode material from coconut shells and product

    CN120208228A

  • A method and product for preparing hard carbon anode materials using coconut shells

    CN120208228B